2020
DOI: 10.1177/1557988320959992
|View full text |Cite
|
Sign up to set email alerts
|

“All My Problems Go Away for 90 Minutes”: How Football and Psychotherapy Improves Young Men’s Mental Health

Abstract: This qualitative research sought to establish the impact of an 8-week program combining football and one-to-one psychotherapy on young males’ mental health, determining the factors that predict help-seeking behaviors in this group of men. Pre- and post-participation focus groups were used as the method of data collection. Six males (19–35 years old; M = 25.5) completed both pre-intervention and follow-up focus groups. Help-seeking behaviors were influenced by the appeal of football and the perception of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Additionally, attention to the needs of young men from diverse social and cultural backgrounds is essential for enhancing the utilization of health services among a wider cohort of young men. This necessitates a shift in focus towards culturally sensitive care and consideration of alternative channels of outreach and engagement, including sporting and religious organizations and community events ( Bird et al , 2019 ; Abotsie et al ., 2020 ; McGrane et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, attention to the needs of young men from diverse social and cultural backgrounds is essential for enhancing the utilization of health services among a wider cohort of young men. This necessitates a shift in focus towards culturally sensitive care and consideration of alternative channels of outreach and engagement, including sporting and religious organizations and community events ( Bird et al , 2019 ; Abotsie et al ., 2020 ; McGrane et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a large-scale student survey in 2018, by UKactive and British universities and Colleges Sport (BUCS) focussed on sport and exercise, has shown that students engaging in physical activity through a gym, or participation in sports, improves wellbeing, academic attainment, and social inclusion, therefore recommending that universities raise awareness of these benefits, and ensure opportunities are available for students to be physically active through a variety of means. More recent research has shown similarly that exercise can help improve wellbeing scores for students (e.g Zuo and Yue, 2020), and a study by McGrane et al (2020) looked at the impact of football and psychotherapy on young male's mental health, finding that a combination of both had beneficial outcomes. Neff (2003aNeff ( , 2003bNeff ( , 2009 is credited with the creation of the term self-compassion and subsequent research has shown how self-compassion can improve wellbeing and happiness, and importantly, is also correlated to reduced anxiety and depression.…”
Section: Sports and Exercise For Wellnessmentioning
confidence: 98%
“…There exists an abundance of research on the benefits of exercise including sports on mental health, including numerous studies related specifically to students (BUCS, 2018;Zuo and Yue, 2020;McGrane et al, 2020). Research has even shown that taking part in university sports club is associated with higher levels of selfcompassion, which correlates positively with help-seeking (Wasylkiw and Clairo, 2018).…”
Section: Sport and Social Activitymentioning
confidence: 99%